TOTAL CHOLESTEROL ANALYSIS FOR DIFFERENTIATING EXUDATES AND TRANSUDATES IN PLEURAL FLUIDS - Efelina Sutanto; Liong Boy Kurniawan; Fitriani Mangarengi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
The aimed of this study is to compare the diagnostic value of pleural fluid total cholesterol and Light’s criteria to determine exudate or transudate. The samples used in this cross-sectional study were pleural fluid specimens sent to the Clinical Pathology Laboratory of the Dr.Wahidin Sudirohusodo Hospital Makassar during the period of August-September 2016. Data were grouped according to the type of effusion then statistically analyzed using nonparametric Mann Whitney U-test. The result of this study showed from 55 samples, there were 22 transudates and 33 exudates. The mean total cholesterol levels of exudate is higher than transudate (p=0.006). By using cut-off value of total cholesterol pleural fluid 56 mg/dL, it had sensitivity 72.7%; specificity 78.8%; Positive Predictive Value (PPV) 81.3% and Negative Predictive Value (NPV) 69.6% while Light’s criteria had sensitivity 97%; specificity 63.6%; PPV 80% and NPV 93.3%. Pleural fluid total cholesterol level with cut-off 56 mg/dL is proposed to be used for differentiating exudate and transudate because it is easier and more simple to perform than Light’s criteria.